Find the solution for y= -1/2 x - 6and y= 7/6 x + 4

1 answer

To find the solution for this system of equations, we can set the two equations equal to each other and solve for x:

-1/2 x - 6 = 7/6 x + 4

First, let's multiply each term by 6 to eliminate the fractions:

-3x - 36 = 7x + 24

Next, let's combine like terms:

-3x - 7x = 24 + 36

-10x = 60

Divide both sides by -10:

x = -6

Now that we have found the value of x, we can substitute it back into either of the original equations to find the value of y. Let's use the first equation:

y = -1/2 (-6) - 6
y = 3 - 6
y = -3

Therefore, the solution to the system of equations is x = -6 and y = -3.
Similar Questions
  1. In a .57 M solution of HOC6H5, .0684% of the acid has been dissociated.a) find the concentrations of all aqueous species in the
    1. answers icon 1 answer
    1. answers icon 2 answers
  2. 1. What is the solution of n^-49=0A. -7 B. 7 C. += 7*** Sorry I couldn't find this symbol D. no solution 2. What is the solution
    1. answers icon 41 answers
    1. answers icon 9 answers
more similar questions